1970
DOI: 10.1177/00220345700490065201
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Fluoride In Vivo by Enamel from Repeated Topical Sodium Fluoride Applications in a Fluoridated Area: Final Report

Abstract: Fluoride acquisition by the deciduous and permanent teeth of schoolchildren who consumed fluoridated water was studied during repeated topical applications in plastic mouth applicators of gel drops containing acidulated phosphate sodium fluoride. The fluoride acquired by the outer enamel from the topical treatments appeared to be permanently bound and progressively increased with the number of treatments completed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…These findings confirm observations from two other fluoridated areas, of 892 [Mellberg et al, 1970] and 1,016 ppm F [M ellberg et al, 1972a] as well as observations from three non-fluori-dated areas, of 680 [Mellberg et al, 1967], 675 [M ellberg et al, 1972b], and 702 ppm F [M ellberg et al, 1973b]. The differences with in these areas are probably due to slight variations in the amount of fluoride in the drinking water and foods as well as differences in the amount of water ingested and analytical error.…”
Section: Discussionsupporting
confidence: 91%
“…These findings confirm observations from two other fluoridated areas, of 892 [Mellberg et al, 1970] and 1,016 ppm F [M ellberg et al, 1972a] as well as observations from three non-fluori-dated areas, of 680 [Mellberg et al, 1967], 675 [M ellberg et al, 1972b], and 702 ppm F [M ellberg et al, 1973b]. The differences with in these areas are probably due to slight variations in the amount of fluoride in the drinking water and foods as well as differences in the amount of water ingested and analytical error.…”
Section: Discussionsupporting
confidence: 91%
“…The va lues for Duraphat were about the same as those found after one application of Dura phat in a previous study [Seppa, 1983]. This suggests that using fluoride varnishes the fluoride content of enamel does not in crease with an increased number of appli cations, as has been found using fluoride gel [Mellberg et al, 1970], The results agree with those of Relief el al. [1983].…”
Section: Discussionsupporting
confidence: 89%
“…Because the natural fluoride content of enamel at various depths is well known [Mellberg et al, 1966[Mellberg et al, , 1970Petersson, 1975;Keeneela\., 1980], the deeper biopsy was made only in treated teeth. The fluo ride content in the deeper layer of treated teeth was found to be slightly higher than that in the superficial layer of control teeth, indicating that fluoride varnishes al so deposit a considerable amount of fluo ride deeper in the enamel which agrees with the findings of Petersson [1975] using Duraphat.…”
Section: Discussionmentioning
confidence: 99%
“…A asenden et al [1972] removed thinner layers (1 ¡am), using a biopsy technique, from permanent teeth of children participating in the present study and found much larger increases in fluoride concentration. The relative val ue of superficial and more deeply located enamel fluoride is open to speculation but it might be expected that long-term anti-caries effects would benefit by increased subsurface fluoride concentrations since sub surface enamel demineralization is characteristic of an early enamel le sion [Bergman and Lind, 1966], Although penetration of fluoride was determined using deciduous teeth, it is to be expected that the findings in permanent teeth would not differ significantly [Mellberg et al, 1970].…”
Section: Discussionmentioning
confidence: 99%